POLIMASSHTABNY GEOINFORMATION MONITORING MIGRATION PROCESSES: GENERAL APPROACHES - Vladimir Sergeyevich Tikunov; Vitaly Semenovich Beloserov; Alexander Nikolaevich Panin; Alexander Alexandrovich Cherkasov (Наука. Инновации. Технологии)
This article discusses common approaches to monitor migration processes based on GIS technologies. Much attention is paid polimasshtabnomu approach in the study. Detail the functional blocks GIS monitoring, as well as the possibility of modeling of migration processes.